Financial Reporting Practice Of Waqf Institutions In Selected Countries And Its Implications To Waqf Institutions In Indonesia - Ataina Hudayat; Achmad Tohirin; Zuraidah Mohd-Sanusi; Siti Achiria (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2017)
Although waqf has been practiced in the community long before other Islamic financial instruments, the management of waqf institutions, especially in the field of accounting information lags behind other Islamic organizations. For example, in Indonesia the Indonesian Accountants Association has published seven accounting standards for Islamic banks (SFAS No. 1 to SFAS No 7), an accounting standard for takaful (SFAS 108), an accounting standard for charity, infaq and zakah (SFAS 109) and an accounting standard for sukuk (SFAS 110). Nevertheless, up until now there is no standard of accounting for waqf institutions published by the Indonesian Accountants Association. Because of the disparity of management waqf than other Islamic organizations, this paper aims to: 1) First, to describe the gap between the standards and practices of financial reporting waqf institutions and other financial institutions in Indonesia; 2) Second, describe the financial reporting practices of waqf in selected countries. This paper did a survey on the practice of accounting information of waqf institutions in selected countries, published in the website of the organization concerned. In general the paper concludes that to develop the accounting standards for waqf institution in Indonesia, could be based on the accounting standards that have been practiced in other Islamic financial institutions. Fund accounting, especially accounting for endowment fund that has been practiced in the United States could also be a reference to establish accounting standards of waqf. In addition, the standard setter bodies could also refer to the practice of waqf reporting in other countries that are more advanced. Keywords: Accounting, Reporting, Waqf Institution.